مسئولية الدولة المستضيفة عن حماية مباني ومقار البعثات الدبلوماسية والقنصلية المعتمدة لديها والموظفين الدبلوماسيين والقنصليين للدول الموفدة في القانون الدولي والشريعة الإسلامية : دراسة مقارنة - عقلا، عقيل بن محمد علي (al-Jami'ah al-Islamiyah al-'Alamiyah, 2017)
This study aims to clarify the responsibility of the host country in protecting the premises of diplomatic and consular missions and diplomatic personnel. It also aims to emphasis that the host country have to take all administrative and security precautions to prevent them from any attempt to break into, sabotage or harm them. The host country is also committed to repair the damage occurred to them, its approved attaches in the missions headquarters or its members. The essence of the international responsibility for breaching the immunity of headquarters stated that the host country have to pay the necessary compensation for the damage on mission premises or members, and the effects of the international responsibility to violators state of immunity headquarters, where it's obligated to take internal measures to prevent the recurrence of illegal actions towards the mission headquarters and doing what is necessary, such as official apology, admit the mistakes, repair the headquarters, or trial the person committing this such act. The study also aims to investigate the cut off of the enjoyment of the mission headquarters inviolability and immunity in sudden emergencies and unexpected cases, which is difficult for the host country to control, and the extent of permissible use of the mission's headquarters in harbouring wanted people in related to security cases. The researcher has adopted in this study several approaches, including descriptive and inductive approaches, deductive approach, and critical analysis approach of the laws and Vienna Convention, to critique and offer opinions of scholars with respect to the Convention. The researcher found that there is absence of any law to deter the host country, which may affect the friendly relations between the approved state of the mission and the host state. This could be up to cut ties, freezing it, armed conflict (war), and incomplete the purposes and tasks of diplomatic and consular missions. In the global level, it shows that the host country does not respect its commitments and do not meet international adversely, which may affect the national interests and cut its foreign relations.